1999
DOI: 10.1002/(sici)1097-0061(199905)15:7<563::aid-yea398>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the KEX1 gene inPichia pastoris allows expression of full-length murine and human endostatin

Abstract: By using molecular oxygen bis(μ‐oxo)dicopper(III) complexes can be produced from CuI complexes with ligand LX (LX=p‐substituted N‐ethyl‐N‐[2‐(2‐pyridyl)ethyl]‐2‐phenylethylamine; X=OMe, Me, H, Cl, NO2) in which the benzylic position of the ligand is activated and hydroxylated by the Cu2O2 core (see reaction scheme). Detailed characterization of this new C−H bond activation reaction by the bis(μ‐oxo)dicopper(III) core reveals important information on the fundamental chemistry underlying copper monooxygenase rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 18 publications
(18 reference statements)
1
20
0
Order By: Relevance
“…Thus, the N-terminal signal sequence in K28 pptox functions equally effectively in all four yeast genera, indicating that it might have the potential for being used as a novel and unique signal sequence suitable for foreign protein secretion. Furthermore, this is the first time that a biologically active virus toxin has been successfully expressed and secreted in C. glabrata and P. pastoris, confirming more recent reports on the existence of Kex2p/Kex1p homologous processing machinery that is required for the in vivo processing and maturation of protein precursors (1,2).…”
Section: Resultssupporting
confidence: 84%
“…Thus, the N-terminal signal sequence in K28 pptox functions equally effectively in all four yeast genera, indicating that it might have the potential for being used as a novel and unique signal sequence suitable for foreign protein secretion. Furthermore, this is the first time that a biologically active virus toxin has been successfully expressed and secreted in C. glabrata and P. pastoris, confirming more recent reports on the existence of Kex2p/Kex1p homologous processing machinery that is required for the in vivo processing and maturation of protein precursors (1,2).…”
Section: Resultssupporting
confidence: 84%
“…Despite intensive efforts, large quantities of recombinant protein sufficient for clinical trials were not available until recently (6). The difficulties in protein production, long-term storage of bioactive protein, and the cumbersome daily administration may be overcome through transfer of the endostatin gene.…”
mentioning
confidence: 99%
“…When Hirudin was expressed in P. pastoris it was found that the molecule had degraded products where up to three amino acids were clipped from the C-terminus [25]. When human and murine endostatin were expressed in P. pastoris the C-terminal lysine was clipped [13]. In both the cases, inactivation of the KEX1 gene was helpful to express the full length proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus oryzae also has an ortholog of Kex1 termed KexA and displays a serine-type carboxypetidase activity and a broader substrate [12]. Amino acid comparison of P. pastoris and S. cerevisiae Kex1protein shows only 36% identity and 43.7% similarity [13]. Nevertheless, amino acid residues involved in the catalytic triad of S. cerevisiae (Ser198, Asp406 and His470) are conserved [14].…”
Section: Introductionmentioning
confidence: 99%